Convergence of generic infinite products of affine operators. (1999) - Reich, S.; Zaslavski, A. J.
Abstract : We establish several results concerning the asymptotic behavior of random infinite products of generic sequences of affine uniformly continuous operators on bounded closed convex subsets of a Banach space. In addition to weak ergodic theorems we also obtain convergence to a unique common fixed point and more generally, to an affine retraction.